Pengaruh Motivasi Kerja dan Kompetensi Terhadap Kinerja Pegawai Dengan Disiplin Kerja Sebagai Mediasi (Studi kasus Di Lingkungan Kantor Kecamatan Junrejo Kota Batu) - Mohammad Faizi; Jamal Abdul Nasir; Suprayitno Suprayitno (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2021)
The purpose of this study was to test and analyze the effect of work motivation on work discipline, to test and analyze the effect of competence on work discipline, to test and analyze the effect of work motivation on employee performance, to test and analyze the influence of competence on employee performance, to test and analyze the effect of work discipline on employee performance, to test and analyze the effect of work motivation through work discipline on employee performance, to test and analyze the effect of competence through work discipline on employee performance. This research is a quantitative research using explanatory research. The results showed that: (i) Work motivation had a significant effect on work discipline. (ii) Competence had a significant effect on work discipline. (iii) Work motivation has a significant effect on employee performance. (iv) Competence has a significant effect on employee performance. (v) Work discipline has a significant effect on employee performance. (vi) Work motivation through work discipline has a significant effect on employee performance. (vii) Competence through work discipline has no significant effect on employee performance.